STRATEGI PIMPINAN PONDOK PESANTREN DALAM MENINGKATKAN KUALITAS PENDIDIKAN AKHLAK DI PONDOK PESANTREN HIDAYATULLAH KABUPATEN FAKFAK - MOHAMMAD RAMDAN; Surahman Amin; Muhammad Huzain (Al-Mumtaz: Jurnal Manajemen Pendidikan Islam, 2024)
The study aims: 1) to describe the strategies implemented by the leader of the Islamic Boarding School to improve the quality of moral education at the Hidayatullah Sekru Islamic Boarding School, Fakfak Regency. (2) To describe the supporting and inhibiting factors faced by the leader in improving the quality of moral education at the Hidayatullah Sekru Islamic Boarding School, Fakfak Regency. This research applied a descriptive qualitative approach and was conducted at the Hidayatullah Sekru Islamic Boarding School, Fakfak Regency. Primary data sources were Islamic boarding school leaders as the main informants and ustadz/Ustadzah and female students as additional informants. Secondary data sources were books, books, magazines, internet, reports and documentation. Data was collected through observation, interviews and documentation. Data analysis was through data reduction, data presentation, and drawing conclusions. The research results show that the Islamic Boarding School Leader implements several main strategies: 1) Integrating moral values in the formal and non-formal education curriculum. 2) Carrying out intensive training through religious activities such as recitation, halaqah, and yellow books recitation. 3) Empowering a conducive environment by upholding discipline and example by ustadz and leaders. 4) Strengthening the relationship between Islamic boarding schools and parents to ensure continuity of moral education at home. Supporting factors are the strong commitment of the Islamic boarding school leader, support from the ustadz, and the high enthusiasm of the students and parents in participating in moral education programs. Then, the inhibiting factors are limited facilities and resources, differences in student backgrounds which influence acceptance and understanding of moral values, and challenges in maintaining consistent discipline in the Islamic boarding school environment. The implications of this research are: 1) facilities and resources in the Islamic boarding school environment must be improved to support the moral education program optimally. 2) continuous training for ustadz and caregivers in moral learning methods is necessary, along with more intensive collaboration between Islamic boarding schools and student’s parents to create an environment for moral education both in the Islamic boarding school and at home.